Perencanaan Penggantian Komponen Mobil Penumpang Muatan 15 Orang Periode 2026 - Muhamad Dwi Kurniawan; Syamsul Hadi; Muhammad Rangga; Fernanda Yudha Firmansyah; Marcellino Yoga (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
The problem with a passenger car with a capacity of 15 people lies in its unscheduled maintenance and having broken down on the road. The purpose of component replacement planning is to obtain component replacement costs, maintenance and repair schedules for the 2026 period, and the maintenance cost-to-profit ratio. The planning method includes collecting previous maintenance data, applying the inspection-replace-repair-overhaul (IRRO) method, evaluating component conditions, estimating component lifespan, estimating labor costs, estimating supporting equipment to be used in maintenance, estimating the time to replace spare parts or reinstall repaired components, estimating maintenance and repair costs for the 2026 period, and calculating the maintenance cost-to-profit ratio. The results of component replacement planning obtained costs for the 2026 period are IDR 11,780,000 with an estimated passenger car rental rate of IDR 800,000/24 ​​hours (day) which has the potential to be rented for 4,320 hours/year, and the ratio of maintenance costs to profits is 10.33% which implies that passenger cars with a capacity of 15 people are still prospective to generate profits and are suitable for use for the next few years.